2017
DOI: 10.1007/s10802-017-0262-0
|View full text |Cite
|
Sign up to set email alerts
|

Social Adversity and Antisocial Behavior: Mediating Effects of Autonomic Nervous System Activity

Abstract: The display of antisocial behaviors in children and adolescents has been of interest to criminologists and developmental psychologists for years. Exposure to social adversity is a well-documented predictor of antisocial behavior. Additionally, measures of autonomic nervous system (ANS) activity, including heart rate variability (HRV), pre-ejection period (PEP), and heart rate, have been associated with antisocial behaviors including rule-breaking and aggression. Social neuroscience research has begun to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 84 publications
(98 reference statements)
2
24
0
Order By: Relevance
“…This again could be a function of a poor translation of current aggression measures to female aggressive behavior. Regardless, additional studies looking at measures of autonomic activity such as heart rate and skin conductance level similarly saw no relationship between behavior problems and physiological responding in girls ( Isen et al, 2010 ; Fagan et al, 2017 ). Some posit that social and environmental influences are stronger, if not dominant, in predicting female externalizing behaviors, and that there could be sex-specific genetic effects driving the development of these behaviors ( Beauchaine et al, 2008 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This again could be a function of a poor translation of current aggression measures to female aggressive behavior. Regardless, additional studies looking at measures of autonomic activity such as heart rate and skin conductance level similarly saw no relationship between behavior problems and physiological responding in girls ( Isen et al, 2010 ; Fagan et al, 2017 ). Some posit that social and environmental influences are stronger, if not dominant, in predicting female externalizing behaviors, and that there could be sex-specific genetic effects driving the development of these behaviors ( Beauchaine et al, 2008 ).…”
Section: Discussionmentioning
confidence: 98%
“…Exclusion criteria for participation included children diagnosed with psychiatric disorder, intellectual disability, or a pervasive developmental disorder. A detailed description of the study can be found elsewhere ( Gao et al, 2015 , 2016 ; Fagan et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Functional failure of the sympathetic part of the ANS is accompanied by a compensatory increase in the activity of the parasympathetic department of the ANS. HRV may be more than just an index of healthy heart function and may in fact serve as an easily measured output of the brain's integrative system for adaptive regulation (Thayer et al, 2012, Fagan et al, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…One widely used measure of autonomic nervous system (ANS) activity is the beat-to-beat variations in cardiac rhythm as indexed by heart rate variability, which is currently one of the most widespread methods for the quick assessment of the functional state of different autonomic regulation elements and hence the whole body (Fagundes et al, 2011, Jarczok et al, 2013, Voltas et al, 2016. HRV has been independently associated with morbidity and mortality, especially in relation to cardiovascular disease (Jarczok et al, 2013, fatigue (Fagundes et al, 2011), work stress (Loerbroks et al, 2010), and psychological status (Fagan et al, 2017, Dzhebrailova & Suleymanova, 2012, Koenig et al, 2018. Psychological stress is thought to be a dominant factor in the lives of many people.…”
Section: Introductionmentioning
confidence: 99%
“…We predicted that there would be a great amount of overlap between externalizing behavior and CU traits in explaining brain activation. Finally, since prior research has implicated low IQ and high social adversity in antisocial behavior (e.g., Moffitt et al, 1981;Fagan et al, 2017), we included measures of IQ and social adversity as covariates. Sex and pubertal status were also included as covariates given that sex differences in the structural and functional abnormality have been found in antisocial populations (e.g., Raine et al, 2011;Visser et al, 2013) and an increasing number of studies have illustrated the effects of puberty on brain structure (Urošević et al, 2014;Herting and Sowell, 2017).…”
Section: Introductionmentioning
confidence: 99%